Silver Empowerment Fostering Strengths and Connections for an Age-Friendly Society - Van Regenmortel, Tine; De Witte, Jasper (Leuven University Press, 2023)
The strengths and opportunities of ageing and the ageing populationSilver empowerment is a valuable paradigm to improve care and support systems for older persons. It aims to counteract the dominant image of ageing, which is all too often one of decline, dependency and vulnerability, and rather sees ageing and the ageing population as a challenge that opens up new opportunities. By focusing on the strengths and connections of older persons, silver empowerment strives for an inclusive, age-friendly society that will allow everyone to grow old with dignity and meaning. In this book, leading academics from a variety of disciplines discuss ways to enhance the empowerment of older persons in practice. Covering a wide range of topics such as resilience, loneliness, community-based care, the interplay between formal and informal care, the inclusion of older persons' perspectives in research and care, and empowering policy, Silver Empowerment is of interest to academics, policy makers and practitioners interested in empowerment and care and support systems for older persons.Contributors: Jasper De Witte (KU Leuven), Tine Van Regenmortel (KU Leuven / Tilburg University), Leen Heylen (Thomas More), Benedicte De Koker (HOGENT), Dimitri Mortelmans (University of Antwerp), Anja Declercq (KU Leuven), Elena Bendien (Leyden Academy on Vitality and Ageing), Susan Woelders (Leyden Academy on Vitality and Ageing), Tineke Abma (Leiden University Medical Center / Leyden Academy on Vitality and Ageing), Meriam Janssen (Tilburg University), Katrien Luijkx (Tilburg University), Aukelien Scheffelaar (Tilburg University), Annerieke Stoop (Tilburg University), Jozef Pacolet (KU Leuven), Gregorio Rodríguez Cabrero (University of Alcalá), Simón Sosvilla-Rivero (Complutense University of Madrid), Katrien Steenssens (KU Leuven).Ebook available in Open Access.This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).